The Legal Status of the Judicial Council of Montenegro as One of the Determinants of the Process of Accession to the European Union: A Theoretical and Legal Analysis - Nowak, Krystian (PRAWO i WIĘŹ, 2025)
By defining priorities and setting requirements for judicial independence, the EU strengthens democratic governance mechanisms. This is demonstrated by the EU's requirement to ensure the independence of the judiciary, which involves delineating the proper position of the Judicial Council. This is a key element in the evolution of the institutional relationship between political power and the body that aims to act as guarantor of the rule of law and controller of the supreme authority's powers. In this paper, the author analyses the provisions of the Constitution and ordinary legislation that define the Judicial Council's constitutional position within Montenegro's political system. Particular attention is paid to the manner in which the council's members are elected in the context of Montenegro’s European aspirations. The paper focuses on demonstrating the council’s legal status, highlighting its composition and competences, and the status of its members – factors that are crucial for establishing the council's independence guarantees. Additionally, the author attempts to answer the question of whether Montenegrin normative solutions meet European standards within the scope of the research. The Judicial Council of Montenegro is a specialised body with wide-ranging competences in the judiciary, though changes to the composition of the council and the mode of election of its members are required.